Understanding the regulation of plant primary metabolism by integrating metabolomics and physiological approaches - Lima, Valéria Freitas (2023)
In recent years, research on the plant metabolic regulation has significantly advanced thanks to metabolomics, mainly by the emergence of 13C-metabolic flux analysis (13C- MFA), which is revealing complex network patterns of metabolic pathways. Despite significant progress, accurately mapping patterns of in vivo metabolic flux remains challenging. While approaches based on nuclear magnetic resonance have resolved small networks with high accuracy, mass spectrometry methods have been hindered by the lack of atomic-level positional information. This Thesis addresses this limitation through an establishment of a novel approach using gas chromatography (GC) coupled with mass spectrometry (MS) to precisely determine 13C-positional labeling in key metabolites of central metabolism. Validated with reference substances positionally labeled with 13C via GC-electron impact-MS and GC-atmospheric pressure chemical ionization-MS, this approach showcases efficacy in analyzing previous 13C-MFA data in leaves and guard cells. New insights were obtained into glucose, which has carbon atoms preferentially labeled by photosynthesis and gluconeogenesis. Additionally, we provide a platform to investigate 13C-incorporation into malate and glutamate derived from phosphoenolpyruvate carboxylase (PEPc). Our findings revealed that gluconeogenesis and PEPc-mediated CO2 assimilation into malate are activated in a light-independent manner in guard cells, while fluxes from glycolysis and PEPc towards glutamate are restricted by the mitochondrial thioredoxin system in illuminated leaves. We also explored the metabolic dynamics of guard cells after PEPc-mediated CO2 assimilation, under darkness or during dark-to-light transition. Although metabolic changes were largely consistent between dark-exposed and illuminated guard cells, the influence of light on metabolic network structures was evidenced by increased 13C-enrichment in sugars and metabolites associated with the tricarboxylic acid (TCA) cycle. Additionally, given the impact of climate change on plants performance worldwide, we investigated the effects of drought, high temperatures, and high CO2 concentration on a fern (Nephrolepis exaltata) and a typical angiosperm, Brassica oleracea. While B. oleracea exhibited significant physiological responses to high CO2 concentration, independent of other stress conditions, the fern was mostly unresponsive to all stresses at the physiological level. Lipid and primary metabolite levels in B. oleracea changed in response to stress, whereas these metabolic responses were absent in the fern. Our findings suggest differential impacts of climate change on ferns and angiosperms. 12 Collectively, the integration of metabolomics and physiological analyses used in our studies provides comprehensive insights into mechanisms underlying plant metabolic regulation and adaptation, offering innovative strategies for metabolomics analysis and contributing to knowledge of the environmental responses of plants, from different groups, to the conditions of a world undergoing climate change.